Management and Economic Development - Negandhi, A.R. author. aut Link
192 p.
Keywords: The ping-pong diplomacy and its aftermath discussion, coupled with the entry of communist China into the United Nations and the subsequent expulsion of Taiwan, will generate considerable political dialogue about the changing balance of power and the fate of the other China. These political discussions will obviously overshadow the true role and function of the existence of Taiwan. Given the time, Taiwan could become a model for the development process for other emerging countries. Taiwan's experience with eco nomic development has real relevance for many countries. For exam ple, in less than two decades Taiwan has achieved the industrial and economic growth that should well make it the envy of nearly all other developing nations. Its per capita income is exceeded only by Japan among the countries of the Far East. Yet, despite vigorous economic and industrial growth, obvious breakdowns in this economic progress come into view. The lack of managerial input threatens to become a real bottleneck. The study reported in this volume examines the feasibility and utility of transferring advanced management know-how and practices into the industrial enterprises in Taiwan in order to generate further economic and industrial growth. The study itself concerns management practices and effectiveness of American subsidiaries, Japanese sub sidiaries, and comparable local firms in Taiwan.